Huygens' Metasurfaces Enabled by Magnetic Dipole Resonance Tuning in Split Dielectric Nanoresonators - Liu, Sheng; Vaskin, Aleksandr; Campione, Salvatore; Wolf, Omri; Sinclair, Michael B.; Reno, John; Keeler, Gordon A.; Staude, Isabelle; Brener, Igal (Nano Letters, 2017)
Dielectric metasurfaces that exploit the different Mie resonances of nanoscale dielectric resonators are a powerful platform for manipulating electromagnetic fields and can provide novel optical behavior. In this work, we experimentally demonstrate independent tuning of the magnetic dipole resonances relative to the electric dipole resonances of split dielectric resonators (SDRs). By increasing the split dimension, we observe a blue shift of the magnetic dipole resonance toward the electric dipole resonance. Therefore, SDRs provide the ability to directly control the interaction between the two dipole resonances within the same resonator. For example, we achieve the first Kerker condition by spectrally overlapping the electric and magnetic dipole resonances and observe significantly suppressed backward scattering. Moreover, we show that a single SDR can be used as an optical nanoantenna that provides strong unidirectional emission from an electric dipole source.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Dielectric metasurfaces; GaAs; Huygens' metasurface; III-V semiconductors; Kerker condition; resonant tuning